Total Knee Arthroplasty Is Safe in Jehovah's Witness Patients—A 12-Year Perspective - Wolfson, Theodore S.; Novikov, David; Chen, Kevin K.; Kim, Kelvin Y.; Anoushiravani, Afshin A.; Deshmukh, Ajit J.; Lajam, Claudette M. (The Journal of Knee Surgery, 2020)
Despite the evolution of blood management protocols, total knee arthroplasty (TKA) occasionally requires allogeneic blood transfusion. This poses a particular challenge for Jehovah's Witnesses (JW) who believe that the Bible strictly prohibits the use of blood products. The aim of this study was to compare JW and a matched-control cohort of non-JW candidates undergoing TKA to assess the safety using modern blood management protocols. Fifty-five JW patients (63 knees) who underwent TKA at our institution between 2005 and 2017 were matched to 63 non-JW patients (63 knees). Patient demographics, intraoperative details, and postoperative complications including in-hospital complications, revisions, and 90-day readmissions were collected and compared between the groups. Additionally, subgroup analysis was performed comparing JW patients who were administered tranexamic acid (TXA) between the two groups. Baseline demographics did not vary significantly between the study cohorts. The mean follow-up was 3.1 years in both the JW and non-JW cohorts. Postoperative complications, including in-hospital complications (7.9 vs. 4.8%; p = 0.47), revision TKA (1.6 vs. 1.6%; p = 1.00), and 90-day readmission (1.6 vs. 4.8%; p = 0.31) were not significantly different between the JW and non-JW groups. Subgroup analysis demonstrated JW patients who received TXA had a significantly lower decline in postoperative hemoglobin (Hgb) (8.6 vs. 14.0%; p < 0.01). At a follow-up of up to 12 years, JW patients who underwent TKA have outcomes equivalent to non-JW patients without the need for transfusion. Our findings support that surgeons are more likely to optimize JW patients preoperatively with iron and folate supplementation. Despite these variations in preoperative optimization efforts, no significant difference with regard to Hgb or hematocrit levels was demonstrated. Level of evidence is III, retrospective observational study.
Keywords: total knee arthroplasty; blood transfusion; Jehovah's Witnesses; survivorship; blood management protocol